Neurotrophins: neuroimmune interactions in human atopic diseases - Weihrauch, Tobias; Limberg, Maren; Gray, Natalie; Schmelz, Martin; Raap, Ulrike (International journal of molecular sciences, 2023)
Allergic diseases are accompanied by a variety of symptoms such as pruritus, coughing, sneezing, and watery eyes, which can result in severe physiological and even psychological impairments. The exact mechanisms of these conditions are not yet completely understood. However, recent studies demonstrated a high relevance of neurotrophins in allergic inflammation, as they induce cytokine release, mediate interaction between immune cells and neurons, and exhibit different expression levels in health and disease. In this review, we aim to give an overview of the current state of knowledge concerning the role of neurotrophins in atopic disorders such as atopic dermatitis, allergic asthma, and allergic rhinitis.